1981
DOI: 10.1159/000214908
|View full text |Cite
|
Sign up to set email alerts
|

Peptidhormone LH, FSH, TSH, Prolaktin, β-HCG und PTH bei Patienten mit urogenitalen Tumoren

Abstract: Die Werte für die Peptidhormone LH, FSH, TSH, Prolaktin, β-HCG und Parathormone schwanken erheblich bei Patienten mit urogenitalen Tumoren. β-HCG ist nur beim Chorionkarzinom, beim Hodenteratom und beim embryonalen Hodenkarzinom erhöht und steigert die Sekretion von Prolaktin. Serum-TSH und Prolaktin sind beim Nierenkarzinom auffällig verändert. Nach Nephrektomie bei fortgeschrittenem Tumorstadium persistiert der pathologisch erhöhte TSH-Gehalt, während sich häufiger emiedrigte PTH-Werte in dieser Gruppe nach-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
1
Order By: Relevance
“…At the same time clinical biochemical research revealed that serum levels of luteinizing hormones (LH), follicle-stimulating hormones (FSH), thyroid-stimulating hormones (TSH), luteotropic hormones (prolactin, PRL), human chorionic gonadotropin (beta-HCG) hormones, and parathyroid hormones (PTH) were significantly modulated in patients with urogenital tumors including RCC. After nephrectomy, PTH was frequently suppressed in these patients (20). Prolactin elevation was found in 45% of ccRCC patients regardless of the stage of the disease.…”
Section: Hormone Signaling Pathways As Treatment Targets In Renal Celmentioning
confidence: 91%
See 1 more Smart Citation
“…At the same time clinical biochemical research revealed that serum levels of luteinizing hormones (LH), follicle-stimulating hormones (FSH), thyroid-stimulating hormones (TSH), luteotropic hormones (prolactin, PRL), human chorionic gonadotropin (beta-HCG) hormones, and parathyroid hormones (PTH) were significantly modulated in patients with urogenital tumors including RCC. After nephrectomy, PTH was frequently suppressed in these patients (20). Prolactin elevation was found in 45% of ccRCC patients regardless of the stage of the disease.…”
Section: Hormone Signaling Pathways As Treatment Targets In Renal Celmentioning
confidence: 91%
“…Even patients without paraneoplastic syndromes experience frequent changes that are directly caused by RCC (20), although only a single case of hyperprolactinemia induced by RCC has thus far been reported (58).…”
Section: Prolactin (Prl)mentioning
confidence: 99%
“…For instance, serum androgen level is one of the important indicators in the initial diagnosis of the majority of PrCa ( 30 , 31 ), and clinical endocrine therapy of PrCa is mainly to reduce androgen levels and to inhibit the function of the androgen receptor ( 32 ). Renal cell carcinoma may also be hormone-related cancer, given that clinical studies have found that multiple hormone receptors were highly expressed in RCC tumor tissues ( 33 ) and abnormal hormone levels are of vital importance for RCC development ( 34 , 35 ). In a sense, BRCA, PrCa, and RCC are all hormone-related cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest a possible gonadotropin secretion by the tumor, but there is no definitive diagnosis. We have found three clinical cases of LH secretion, two of them by pancreatic tumors (20,21) and one by an adrenocortical tumor (22), and gonadotropin secretion by urogenital tumors (23). Exceptional cases of ovarian hyperstimulation associated with severe primary hyperthyroidism (24) and with granulosa cell tumors (25) have been described.…”
Section: Case Reportmentioning
confidence: 98%